Only three cycles of nivolumab showed remarkable durable response and reversible myeloradiculoneuropathy in a patient with metastatic papillary renal cell carcinoma type 2. Issue 3 (17th February 2021) - Iwasaki, Kazunori; Shin, Toshitaka; Inoue, Toru; Shibuya, Tadamasa; Hirai, Kenichi; Ando, Tadasuke; Mimata, Hiromitsu
Abstract : Introduction: The efficacy of nivolumab for non‐clear cell renal cell carcinoma is still unclear. We present a rare case of metastatic papillary renal cell carcinoma remarkably responded to nivolumab but developed myeloradiculoneuropathy as immune‐related adverse event. Case presentation: The patient had previously undergone radical nephrectomy for right renal mass and was diagnosed as papillary renal cell carcinoma type 2, pT3bN0M0. Three years after the first surgery, he received 3 mg/kg of nivolumab as a second‐line drug for mediastinum lymph nodes and lung metastases. With three cycles of nivolumab, the patient felt progressive weakness of the legs and received two cycles of steroid‐pulse therapy based on the diagnosis of myeloradiculoneuropathy. Although nivolumab therapy has been discontinued, the metastases show radiographic complete response at 2 years after the last nivolumab administration without any additional therapy. Conclusion: Nivolumab may be a promising treatment option for non‐clear cell renal cell carcinoma such as papillary renal cell carcinoma.